How Employer Branding Affects Employer Attractiveness in the Vietnamese Service Industry? - Thi, Minh Ha Nguyen; Nguyen, Thanh Tra; Nguyen, Xuan Loc (International Review of Management and Marketing, 2026)
The quality of human resource relies on whether firms can identify and attract talented employees while other firms also compete aggressively to obtain such workforce. Although prior research focuses on how to conduct employer branding and how it is important to attract potential staff, they have not fully addressed how employer branding affects employer attractiveness. This paper aims at filling this gap in the context of the service industry which significantly emphasizes the role of employees in creating service quality. Our sample includes 358 respondents who have ever searched for information about or considered applying to a specific service company. Using the structural equation modelling, we find that employer branding has a positive effect on corporate reputation which, in turn, increases employer attractiveness. Our findings imply that service firms should recognize the importance of employer branding and improve their employer branding practices. Employer branding is not only good for their reputation but also their attractiveness towards job applicants. If firms fail to have enough resources to invest in all employer branding dimensions, they may set investment priorities based on their resources and capabilities. Moreover, applicants should collect enough information about firms before applying for jobs. Considering employer branding dimensions across potential employers help applicants choose appropriate destinations for their applications.